PENGARUH ASPEK PAJAK DAN ASPEK LAINNYA TERHADAP TINGKAT HUTANG - Stephanie Soerodjo (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2018)
As a developing country, Indonesia shows a quite interesting phenomenon, which is the high rate of debt of many companies in Indonesia. This fact shows that the policy of leverage plays an important role for the viability of the company. The main purpose of this research was to test empirically factors influencing leverage, for there are still inconsistencies in research results from the prior studies. Based on the data of the mining companies listed on BEI for period 2009-2011, in addition of using tax factors that consisted of Corporate tax rate and Non-debt tax shield, influencing the leverage, there are also another factors influencing leverage, which are Investment opportunity set, Profitability, Past debt, Tangibility of fixed assets, Firm size, and Cost of financial distress. The analyzed data are the combination of time series and cross-section data or, panel data, utilizing the regression model supported by the software SPSS 20 on 0,05 or 5% of significance level. The result of the study shows that at the significance level of 0,05 Corporate Tax Rate (0,543), Non–debt Tax Shield (0,518), Investment Opportunity Set (0,442), Tangibility of Fixed Assets (0,544), Firm Size (0,500), and Cost of Financial Distress (0,380) have no significant effect for the leverage. While Profitability (0,028) negatively has significance effect for the leverage at the significance of 0,05. While Past Debt (0,000) has significant positive effect on the leverage at the significance of 0,05.